2022
DOI: 10.1021/acs.biomac.2c01197
|View full text |Cite
|
Sign up to set email alerts
|

Switching the Mode of Drug Release from a Reaction-Coupled Low-Molecular-Weight Gelator System by Altering Its Reaction Pathway

Abstract: Low-molecular-weight hydrogels are attractive scaffolds for drug delivery applications because of their modular and facile preparation starting from inexpensive molecular components. The molecular design of the hydrogelator results in a commitment to a particular release strategy, where either noncovalent or covalent bonding of the drug molecule dictates its rate and mechanism. Herein, we demonstrate an alternative approach using a reaction-coupled gelator to tune drug release in a facile and user-defined mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Recently, Kieltyka and co-workers explored a dynamic assembly system in which the anticancer drug doxorubicin could be incorporated non-covalently into LMWG assemblies by intercalation, or could react with the gelator scaffold via a bond forming reaction. 316 These outcomes could be tuned based on the dynamics of assembly and the formulation strategy. In the case where the drug became covalently coupled to the gelator framework, a greater degree of sustained release was observed.…”
Section: Advanced Technologiesmentioning
confidence: 99%
“…Recently, Kieltyka and co-workers explored a dynamic assembly system in which the anticancer drug doxorubicin could be incorporated non-covalently into LMWG assemblies by intercalation, or could react with the gelator scaffold via a bond forming reaction. 316 These outcomes could be tuned based on the dynamics of assembly and the formulation strategy. In the case where the drug became covalently coupled to the gelator framework, a greater degree of sustained release was observed.…”
Section: Advanced Technologiesmentioning
confidence: 99%
“…In this context, stimuli-responsive gels based on LMWGs could be prospective materials [5]. For instance, gels obtained from Lalanine derivatives [60], hydrazide/benzaldehyde derivatives [61] and small peptide derivatives [62,63] showed potential applications as matrices for the delivery of various…”
Section: Toxicity Of the Gels To Siha Cellsmentioning
confidence: 99%
“…While the Heilshorn lab combined covalent and non‐covalent synthesis on the hydrogel‐level 14 . In addition, the Kieltyka and Eelkema labs showed a covalent versus non‐covalent approach to in‐situ control hydrogel mechanics on the mesoscale 22 …”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, the Kieltyka and Eelkema labs showed a covalent versus non-covalent approach to in-situ control hydrogel mechanics on the mesoscale. 22 Moving from a combined covalent and non-covalent approach to a fully supramolecular approach, the Stupp lab revealed that their thermodynamically favored peptide amphiphiles (PAs) formed long fibers that promoted cell adhesion and survival, while the metastable PAs assembled into short fibers leading to cell death. 21 The Adams lab reported on the controlled self-assembly of small molecules to yield functional materials: by employing short peptides and pH as a trigger, the gelation process and gel mechanics were tuned.…”
mentioning
confidence: 99%